1,6-Conjugate Addition of Carbon Nucleophiles to (E)-2-Styrylchromones: Unexpected Synthesis of a Stereochemically Complex Pentasubstituted Spirocyclohexane - Silva, Eduarda M. P.; Grenda, Kinga; Cardoso, Inês N.; Silva, Artur M. S. (Synlett, 2013)
The regioselective 1,6-conjugate addition of ethyl malonate and malononitrile to (E)-2-styrylchromones is described. A synthesis of novel pentasubstituted spirocyclohexanes discovered during the course of these studies is also discussed. A novel domino multicomponent 1,6-/1,6-/1,4-conjugate addition reaction for the formation of these new spirocyclohexanes is proposed.
Keywords: heterocycles; polycycles; nucleophilic additions; addition reactions; spiro compounds; domino reactions; multicomponent reactions